Recent Trends in Translation Studies An Anglo-Italian Perspective - Laviosa, Sara; Iamartino, Giovanni; Mulligan, Eileen (Cambridge Scholars Publisher, 2021)
This volume offers a snapshot of current perspectives on translation studies within the specific historical and socio-cultural framework of Anglo-Italian relations. It addresses research questions relevant to English historical, literary, cultural and language studies, as well as empirical translation studies. The book is divided into four chapters, each covering a specific research area in the scholarly field of translation studies: namely, historiography, literary translation, specialized translation and multimodality. Each case study selected for this volume has been conducted with critical.